2023
DOI: 10.2147/ijwh.s382235
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Adenocarcinoma Arising from Endometriosis in Abdominal Wall Cesarean Section Scar: A Case Report and Literature Review

Abstract: Background Endometriosis developing in a cesarean section (CS) scar is an unusual event. Malignant transformation arising on the background of scar endometriosis in the abdominal wall is extremely rare. Herein we report a case of clear cell carcinoma (CCC) arising in the abdominal wall from endometriosis tissues following CS and review previous literature. Case Presentation A 48-year-old gravida 2 para 1 female presented with an abdominal wall mass at her CS scar, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This condition may be more common than previously thought and accounted for in literature [ 1 ]. Prompt diagnosis is crucial to prevent delay in treatment as malignant transformation into endometrioid carcinoma, sarcoma, or clear cell adenocarcinoma has been reported [ 16 , 17 ]. A review of 12 cases of AWE demonstrated transformation to clear cell adenocarcinoma with an average age of diagnosis at 45.7 years with a high associated mortality of 25% within 15 months of diagnosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition may be more common than previously thought and accounted for in literature [ 1 ]. Prompt diagnosis is crucial to prevent delay in treatment as malignant transformation into endometrioid carcinoma, sarcoma, or clear cell adenocarcinoma has been reported [ 16 , 17 ]. A review of 12 cases of AWE demonstrated transformation to clear cell adenocarcinoma with an average age of diagnosis at 45.7 years with a high associated mortality of 25% within 15 months of diagnosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, malignant transformation of AWE after Cesarean section has recently increased. Proposed thoughts for this trend are due to a general increase in the number of Cesarean sections from 7% in 1990 to 21% in the present day [ 16 , 18 ]. As a result, the possibility of malignancy should be strongly considered in patients who present with Esquivel’s triad [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation